Institutional mechanisms of (non)representing of interests in Poland in the perspective of analytical sociology: An outline of a research problem - Szklarczyk, Dariusz (Journal of Public Governance, 2014)
The article tentatively discusses representing the interests of employees and employers in Poland from the perspective of analytical sociology. In the first part of the article, particular attention was devoted to social mechanisms as tools used to explain social reality and to the role played in the social mechanisms by institutions. The article also discusses selected issues related to the interest representation of employees and employers that constitute the so-called influence-production process: mobilizing for action, competition, influencing and evaluation of the effects of actions. In conclusion, the author states a need to explain these issues through the implementation of the basic assumption of analytical sociology: the study of social mechanisms.